Case study risk management process in Sapuracrest Petroleum Berhad / Siti Nur Ramizah Long Zainudin - Long Zainudin, Siti Nur Ramizah (2010)
Risk as defined by Emmett J. Vaughan (1996) is the “condition in which there is possibility of an adverse deviation from a desired outcome that is expected or hoped for”. Generally risk is related to the loss, hazards, perils, dangers, threats and the chances and the possibility. It may cause expected or unexpected result. Referring to Emmett J. Vaughan (1996), risk management is defined as a “scientific approach to the problem of dealing with the pure risks by anticipating possible accidental losses and designing and implementing procedures that minimize the occurrence of loss or the financial impact of the losses that do occur”. Risk management is an objective corporate approach to the problem of deciding the best way of controlling the threats to the security of an organisation. Hence, his defined as whole risk management as “the making of decisions concerning risks and their subsequent implementation, and flows from risk estimation and risk evaluation”. Kenneth W. Hollman and Jack E. Forrest (1991) said that “risk management is a logical and continuous process which can be used by managers to approach and solve risk management problems”.